Study of the enhanced electronic and thermoelectric (TE) properties of ZrxHf1−x−yTayNiSn: a first principles study. Issue 115 (5th December 2015) - Rai, D. P.; Shankar, A.; Sandeep; Ghimire, M. P.; Khenata, R.; Thapa, R. K.
Abstract : A density functional theory (DFT) approach employing generalized gradient approximation (GGA) and the modified Becke Johnson (TB-mBJ) potential has been used to study the electronic and thermoelectric (TE) properties of Zr x Hf1− x − y Ta y NiSn. Abstract : A density functional theory (DFT) approach employing generalized gradient approximation (GGA) and the modified Becke Johnson (TB-mBJ) potential has been used to study the electronic and thermoelectric (TE) properties of Zr x Hf1− x − y Ta y NiSn. The presence of an indirect band gap at E F in the parent compound predicts this material to be a small band gap insulator. The substitution of Ta atoms at the Hf site increases the density of states (DOS) at E F which facilitates charge carrier mobility. The influence of Ta content increases the Seebeck coefficient and electrical conductivity, and suppresses the thermal conductivity; as a result the figure of merit ZT is enhanced. We report an increment in ZT value of 36% over the undoped system. The theoretical data were compared with the experimental results.